(untitled) (Trabalho & Educação, 2016)
Prepared as a result of bibliographic research, exploratory, this article discusses the problems inherent in the relationship between work and education, linking these categories to production processes and their implications in the school. This is a critical and reflective analysis of the changes in the world of work and the resulting education, especially the technical and scientific advances, the restructuring of the capitalist production system. In the elaboration of this paper, the theoretical approach utilized adresses in topics the thematics work and education; the relationship between work, education and school in the capitalist society; and the implications of the production process in school education. The study results indicate the importance of education that seeks to overcome the alienation and assume responsibility for the conditions of existence and socio-political-economic and cultural interactions. __ Elaborado como decorrência de pesquisa bibliográfica, de caráter exploratório, este artigo discute a problemática inerente às relações entre trabalho e educação, vinculando essas categorias aos processos produtivos e suas implicações no âmbito escolar. Trata-se de uma análise crítico-reflexiva sobre as transformações no mundo do trabalho e da educação decorrentes, sobretudo, dos avanços técnico-científicos, da restruturação do sistema de produção capitalista. Na organização do texto, o referencial teórico utilizado aborda em tópicos as temáticas trabalho e educação; a relação trabalho, educação e escola na sociedade capitalista; e as implicações do processo produtivo na educação escolar. Os resultados do estudo apontam a importância de uma educação escolar que busque a superação da alienação e assuma responsabilidades quanto às condições de existência e às interações sociopolítico-econômica e cultural.